Limit-point criteria for superlinear differential equations - Mustafa, OG; Rogovchenko, YV (Belgian Mathematical Soc Triomphe, 2004)
For a nonlinear differential equation x + a(t)f(x) = 0, we obtain limit-point criteria by proving first stronger results which guarantee nonexistence of nontrivial bounded (uniformly continuous) L-2-solutions under milder restrictions on the coefficient a(t) and nonlinearity f(x).
Keywords: nonlinear differential equations; second-order; square integrable solutions; bounded solutions; asymptotic behavior; limit-point/limit-eircle classification